Дослідження процесів формування перехідного шару на межі сірий чавун–інтегрований неметалевий наповнювач при одержанні легковагових виливків - Дьяченко, М.М.; Корнієць, І.В. (Physico-technological Institute of Metals and Alloys, 2025)
One of the promising approaches for creating reliable and lightweight structures with specified operational properties is the use of lightweight composite castings with integrated ceramic fillers. The key factor determining the quality of such castings is the bond strength of the transition layer at the metal–ceramic interface. The aim of this work was to study the physicochemical processes of transition layer formation between a melt of gray cast iron SCh200 and two types of integrated ceramic fillers (a liquid glass mixture and expanded clay) during the production of castings using the lost foam casting (LFC) method. The work involved an analysis of thermal regimes and possible chemical reactions. The thermodynamic probability of the formation of silicates (ferrosilite, rhodonite) and capillary phenomena were theoretically analyzed. For modeling, a mathematical heat transfer model implemented in a specialized software package developed at the PTIMA of the National Academy of Sciences of Ukraine was used. Hollow castings (module segments) with integrated fillers were experimentally produced using LFC technology. The structure was investigated using optical microscopy methods. The modeling results revealed differences in the thermal regimes and the dynamics of casting formation for the two filler types. For the system with the liquid glass mixture, a significant temperature gradient formed, indicating active heat absorption and promoting the mechanism of deep capillary impregnation. The experiment confirmed the formation of a pronounced mechanical bonding zone with a depth of 0.5–1.5 mm, with signs of additional chemical interaction. In contrast, for the system with expanded clay, a rapid and uniform heating of the filler due to convection was observed, which determined the mechanism of surface physicochemical interaction and the formation of a thin (0.1–0.3 mm) dense layer. Based on the obtained data, it was established that the pouring temperature of 1430 °C ensures the formation of the transition layer for both filler types. The article compares the mechanisms of transition layer formation for two thermophysically different fillers under the conditions of LFC technology. A relationship is shown between the predicted thermal fields and the thickness of the formed transition layer. The obtained results are useful for the production technologies of lightweight cast parts with local reinforcement.